Animals and Symbolic Values Attributed to Animals in Alevi Mythology - Şahin, Mehmet (Journal of Alevism-Bektashism Studies, 2025)
Myths, regarded as real and sacred as the narrative of truth, address how any form of reality comes into existence, how a particular entity is created, or how any object, whether animate or inanimate, attains its present form and meaning. Considering that every being, living or non-living, possesses a mythical history, it can likewise be asserted that animals, an integral part of the natural world, also have their own mythical past. Throughout human history, people have sought to explain the beings in their environment and to ascribe meaning to them. As a mechanism of interpretation, myths have profoundly shaped human beliefs, as well as their perspectives toward the external world and the beings inhabiting it. The path language of Alevism, formed predominantly within an oral-cultural milieu, is interwoven with mythical and mystical expressions and significations. Alevism, which accommodates many mythic narratives within this unique linguistic framework, has its own distinct mythology. The corpus of Alevi mythology includes explanations concerning how its institutions, beliefs, rituals, and external environment are perceived. For this reason, this subject was chosen as the focus of study in order to provide a clearer understanding of the path language, belief system, and Alevi mythology. This study aims to elucidate how animals are explained in Alevi mythic narratives, which components of the belief system they influence, which elements of belief they help to illuminate, and whether the doctrine of tenasüh (transmigration) has any impact on beliefs concerning animals. In this research, a qualitative methodology and a cultural analysis model were employed. Fieldwork was conducted based on pre-formulated questions, and data were collected through semi-structured interviews. These interviews were recorded with a voice recorder and subsequently transcribed and analyzed. Content analysis was used in examining the data. The study group consisted of dedes, âşıks (minstrels), talips, and village elders representing traditional Alevism who reside in the districts and villages of Amasya, Çorum, Samsun, and Tokat. The research identified mythic narratives concerning how animals such as oxen, fish, snakes and other reptiles, crows, swallows, lions, cats, cranes, pigeons, rabbits, bears, wolves, horses, mules, chickens, and roosters acquired their various attributes, present forms, and symbolic meanings. It was observed that some animals acquired specific physical shapes and characteristic traits through their associations with religious figures such as Gabriel, Eve, Ishmael, Prophet Muhammad, Ali, Hızır, and Hacı Bektaş Veli. Additionally, it was determined that the belief in tenasüh, which holds a prominent position within Alevi thought, significantly shapes the community’s positive or negative attitudes toward animals. Furthermore, the findings indicate that the geographical environment in which Alevis live, along with the economic activities tied to this environment, has contributed to certain animals, especially barn animals, being regarded as more favorable, whereas animals belonging to mountainous habitats tend to be viewed as less acceptable.
Keywords: Alevism; mythology; Alevi mythology; animals; symbol